O diário de bordo como instrumento de reflexão crítica da prática do professor - Lilian Sipoli Carneiro Canete (2010)
This research is situated within the theme of qualification of the protagonist teacher/ producer of knowledge. The purpose was to describe and analyze the written production process in the logbook by five teachers from a private school in Belo Horizonte, teachers of early childhood education and early years of elementary school, seeking to understand the relationship between the writing of this diary and critical reflection of practice. Therefore, we examined how each teacher produced its written records, through the logbook, and verified the contributions of this practice for the configuration of the teachers as critical reflective practitioners. A qualitative approach was applied to analyze and understand the production of logbooks. Besides their own logbooks, a questionnaire, a text produced by the teachers called "thinking about writing" and a semi-structured interview were also used as instruments for data collection. The analysis allowed elucidating the process of writing of the logbook, understanding how each teacher writes and revealing the contents of the diaries. Such analysis also revealed the complexity of the debate about the practice of writing the logbook as an instrument of critical reflection of the teachers. It is hoped that this research contributes to the debate of the relationship between reflection and teaching as it may also bring support to the idea for the qualification of the protagonist teacher/producer of knowledge.